Calcium channel blocker associated lower urinary tract symptoms in males: an Australian retrospective observational study - Hughes, Jeffery; Coles, Mark; Joyce, A. (Radcliffe Medical Press Ltd., 2011)
BACKGROUND: Lower urinary tract symptoms (LUTS) are common and prevalence increases with age. In men, voiding symptoms are more commonly encountered than storage symptoms. LUTS are often associated with chronic diseases but their pathophysiology requires further study. We aimed to determine whether calcium channel blockers (CCBs) worsened, improved or did not alter symptoms of urinary obstruction in males aged 45 years and above with medical conditions associated with urinary obstruction. METHODS: A cohort retrospective observational study was undertaken to identify the effect of the use of CCBs on LUTS in males over 45 years of age. Participants were recruited from four community pharmacies and a general practitioner surgery. Eligible participants provided informed consent and were administered a standardised questionnaire (IPSS) to obtain information on LUTS and quality of life (QOL) prior to and after commencement of CCB therapy. RESULTS: Thirty-eight males were enrolled in the study, and their ages of ranged from 46.2 to 88.7 years, with the mean age being 66.9 years (95% CI: 63.9-69.9). The mean IPPS score prior to commencing a CCB was 3.13 (95% CI: 2.09-4.17) compared to 9.82 (95% CI: 7.83-11.80) whilst on the drug (P<0.001). After adjusting for other medications and conditions which may contribute to LUTS, and for the natural progression of LUTS with ageing, the change remained significant. The increase in IPPS score was associated with a significant decline in the respondents' QOL.CONCLUSION: The results of this study suggest that in middle-aged males the introduction of a CCB may be associated with worsening of LUTS, and an associated decline in QOL, although this will need to be confirmed in large prospective studies. However, given the common use of these agents in males to treat a range of cardiovascular conditions, we would suggest that men prescribed a CCB should be questioned about urinary symptoms before and after commencing treatment.